The hot embolus of 18F-fluorodeoxyglucose - Riffat Hussain; Tariq Mahmood (World Journal of Nuclear Medicine)
Scanning oncological patients with 18F-fluorodeoxyglucose (18F-FDG) for their disease staging, evaluation of treatment response, and monitoring/management has become a standard of care. The use of the radioactive fluorine in the FDG molecule helps establish cell/tissue lines high on glucose consumption and hence metabolically active. Abnormalities are detected on the scan as areas of increased uptake. However, these areas of increased (hot) uptakes do not necessarily translate into a pathological finding. A comprehensive knowledge of the uptakes of the tracer and the potential “pitfalls” that may be associated with them should be known and kept in mind during scan reading. One such pitfall is the “hot clot” or “pulmonary emboli,” and we report two such cases encountered at our setup and discuss their causes and how they should be identified and avoided.